HYBRID FUZZY SECOND-ORDER SLIDING MODE CONTROL SPEED FOR DIRECT TORQUE CONTROL OF DUAL STAR INDUCTION MOTOR - B., Kiyyour*; D., Naimi; A., Salhi; L, . Laggoune (university of eloued جامعة الوادي, 2019)
This paper presents a Speed Fuzzy Second-Order Sliding Mode Control (FSOSMC) for Direct Torque Controlled Dual Star Induction Motor (DTC-DSIM). A DTC uses the instantaneous values of voltage vector where each reference voltage vector is computed with a DTC algorithm. The sliding mode control is characterized by its robustness against modeling disturbances and uncertainties; however, this technique has a major disadvantage which is the phenomenon of chattering that produces torque fluctuations. In order to overcome this drawback, a new control scheme that uses the FSOSMC for speed control is proposed. . It is shown that the proposed control strategy conserves the main advantages of the DTC in addition to reducing considerably the chattering effect. It is also robust against modeling disturbances and uncertainties. Several simulation tests are performed illustrating the high accuracy of the proposed control scheme.
artical
Keywords: Dual star induction motor (DSIM). Direct torque control (DTC). Second-order sliding mode control (SOSMC). Speed fuzzy second-order sliding mode control (FSOSMC)